PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA PANTAI CAROCOK PAINAN PESISIR SELATAN - Ikhlas, Reda; Kasmita, Kasmita; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research aims to know the influence of the service quality to the visitor’s satisfaction in the sights of Carocok Painan Pesisir Selatan. Type of this research is quantitative research (assosiatif) with the causal approach. The population in this study amounted to 66,547 people. The number of samples in the study amounted to 100 people. Using purposive sampling. Data collection techniques using likert scale which have tested the validity and realiability. Technique of data analysis SPSS computer program using 16.00 version. Based on the results of the research that has been done is obtained the following results: (1) The service quality placed very good category (46%). (2) The visitor’s satisfaction are in the very good category (71%). Test results of simple linear regression hypothesis acquired Fcount 135.526. Sig value 0.000 < 0.005, then it can be concluded there was significant influence between the variable X against Y with R square 0.580.Keywords: Quality, Service and Visitor’s Satisfaction